Thermal study of Fe3O4 semiconductor magnetic nanofluids using two photothermal techniques for applications in biomedicine - García-Vidal, U. O.; Jiménez-Pérez, J. L.; Correa-Pacheco, Z. N.; Algatti, M. A. [UNESP]; Gutiérrez-Fuentes, R. (Springer Nature, 2024)
The use of photothermal techniques for measuring the thermal parameters of ferromagnetic nanofluids has been the subject of investigation in several recent studies. In this work, the thermal properties of Fe3O4 nanofluids were investigated using two photothermal techniques: Thermal wave resonance cavity (TWRC) and thermal lens spectrometry (TLS). Fe3O4 nanoparticles were prepared using the precipitation method and characterized using transmission electron microscopy (TEM). A nonlinear increase in thermal diffusivity with nanoparticle concentration was observed, with values ranging from 1.52 × 10–3 cm2/s to 5.46 × 10–3 cm2/s. Comparison between the two techniques revealed differences in accuracy and applicability for different nanoparticle concentrations. These results highlight the importance of selecting the appropriate technique based on the specific characteristics of the nanofluid under study. In conclusion, this study provides a deeper understanding of the thermal properties of Fe3O4 nanofluids and underscores the potential of photothermal techniques in characterizing these materials for various applications, including magnetic hyperthermia for cancer treatment.